2013
DOI: 10.1136/annrheumdis-2012-202850
|View full text |Cite
|
Sign up to set email alerts
|

Osteitis and synovitis, but not bone erosion, is associated with proteoglycan loss and microstructure damage in the cartilage of patients with rheumatoid arthritis

Abstract: Objectives To investigate the relation between anatomic changes of the synovium, the bone, the bone marrow and the cartilage to biochemical properties of the cartilage in patients with rheumatoid arthritis (RA). Methods 33 patients with RA received 3-T MRI scans of the metacarpophalangeal joints. Two independent methods, (A) the delayed gadolinium enhanced MRI of the cartilage (dGEMRIC, T2-mapping), which was used to assess the biochemical properties of the cartilage; (B) synovitis, osteitis and bone erosions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…11 In the past, cartilage composition has been compared with the RAMRIS scoring. 4 A strong correlation between the degree of osteistis as well as synovitis with low dGEMRIC and high T2 values has been reported. 4 In their study, synovitis severity was assessed on a semiquantitative level.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…11 In the past, cartilage composition has been compared with the RAMRIS scoring. 4 A strong correlation between the degree of osteistis as well as synovitis with low dGEMRIC and high T2 values has been reported. 4 In their study, synovitis severity was assessed on a semiquantitative level.…”
mentioning
confidence: 94%
“…4 A strong correlation between the degree of osteistis as well as synovitis with low dGEMRIC and high T2 values has been reported. 4 In their study, synovitis severity was assessed on a semiquantitative level. A validated method for the estimation of synovitis is dynamic contrastenchanced (DCE) MRI with its proven feasibility to describe the disease activity in RA patients.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, we sought to use CECT imaging as method to examine the relationships between common cartilage and bone properties towards the development of the metacarpal as a new model for early-stage OA. Although previous publications showcase dGEMRIC for clinical examination of MCPJ cartilage [2224], and a novel nanoparticle CT contrast agent reflected GAG distribution in metacarpal cartilage [25], no previous imaging reports directly examine the relationships between cartilage GAG content and mechanical properties with bony changes in the metacarpal. Herein, we propose the human metacarpal as an appropriate ex vivo model for the study of early OA by demonstrating the relationships between cartilage CECT attenuation, GAG content and distribution, compressive modulus, and subchondral bone properties using CECT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Herz et al . reported that both synovitis and bone marrow edema were associated with cartilage damage in the metacarpophalangeal joints of patients with RA. Other researchers have suggested that the matrix metalloproteinase and matrix‐degrading enzymes released by the inflammatory cells in the synovium are responsible for cleaving cartilage components, with local chondrocytes subsequently synthesizing and locally releasing cytokines, which accelerates the switch from an anabolic to a catabolic state in the cartilage.…”
Section: Discussionmentioning
confidence: 99%